Accommodation or deterrence in the face of commercial piracy : the impact of intellectual property rights protection - Lu, Yuanzhu. (2013)
In this paper, we study when the original product developer makes costly investment to deter a commercial pirate in a given regime of intellectual property rights (IPR) protection. We find that when the consumers' tastes are sufficiently diverse and the IPR protection is weak, it is profitable for the original producer to accommodate the pirate. In all other cases, it is profitable to deter. In the comparative statics analysis, we find a non-monotonic relationship between the optimal level of deterrence and the degree of IPR protection in the economy. We also find interesting relationships between the rate piracy and other parameters like the strength of IPR protection, consumers' tastes, and quality of the pirated product. We find that from the commercial pirate's point of view, the most profitable way to survive in the market is to produce a pirated product of moderate quality.